Analysis of Work Safety Climate Based on Demographic Characteristics in the Phosphoric Acid Industry Using Radar Plot - Aprilia Dwi Purwanti; Dayinta Annisa Syaiful; Endang Dwiyanti (Universitas Airlangga, 2023)
Introduction: Phosphoric acid production has not been achieved in the phosphoric acid industry due to unsafe actions and conditions influenced by various factors, including workplace safety. The work safety climate can measure certain perceptions of safety factors in the workplace and has seven dimensions. The demographic characteristics have a relationship with the perceptions of working safety. This study aims to analyze the work safety climate based on demographic characteristics in the phosphoric acid industry using a radar plot. Methods: The research design was a descriptive quantitative method with a cross-sectional approach. The population of the study is 44 workers in the phosphoric acid industry, with a total sampling of 44 employees. The dependent variable of the study was the work safety climate, and the independent variable was the demographic characteristics. The instrument employs NOSACQ-50 (50 questions) and analyzes the data with frequency tables and radar plot diagrams. Results: Dimensions management safety priority, commitment and competence were classified as good. The work safety climate is good, based on education level and age category. The work safety dimension based on job position is classified as relatively bad. Conclusion: The best dimension of work safety climate is in the foreman job position, the dimension of work safety climate is best at the education level after high school graduation, and the dimension of work safety climate is best at all age categories.